2007
DOI: 10.1242/jcs.03351
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the proteasome interaction with the Sec61 channel in the endoplasmic reticulum

Abstract: Biogenesis of secretory proteins requires their translocation into the endoplasmic reticulum (ER) through the Sec61 channel. Proteins that fail to fold are transported back into the cytosol and are degraded by proteasomes. For many substrates this retrograde transport is affected by mutations in the Sec61 channel, and can be promoted by ATP and the 19S regulatory particle of the proteasome, which binds directly to the Sec61 channel via its base. Here, we identify mutations in SEC61 which reduce proteasome bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 45 publications
(134 reference statements)
1
57
0
Order By: Relevance
“…Although the identities of the components that comprise the retrotranslocation channel remain unclear, Sec61 complex and Derlin-1 are possible candidates (Knop et al 1996;Pilon et al 1997;Willer et al 2008;Schafer and Wolf 2009). Sec61 complex has been reported to interact with several ERAD substrates and ERAD machineries including proteasome, TRAP complex, SPP (signal peptide peptidase), PDI, and BAP31 Pilon et al 1997;Loureiro et al 2006;Nagasawa et al 2007;Ng et al 2007;Wang et al 2008;Lee et al 2010). Derlin-1 was initially reported to be important for the extraction of MHC class I molecules from the ER membrane in cytomegalovirus-infected cells (Lilley and Ploegh 2004;Ye et al 2004).…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…Although the identities of the components that comprise the retrotranslocation channel remain unclear, Sec61 complex and Derlin-1 are possible candidates (Knop et al 1996;Pilon et al 1997;Willer et al 2008;Schafer and Wolf 2009). Sec61 complex has been reported to interact with several ERAD substrates and ERAD machineries including proteasome, TRAP complex, SPP (signal peptide peptidase), PDI, and BAP31 Pilon et al 1997;Loureiro et al 2006;Nagasawa et al 2007;Ng et al 2007;Wang et al 2008;Lee et al 2010). Derlin-1 was initially reported to be important for the extraction of MHC class I molecules from the ER membrane in cytomegalovirus-infected cells (Lilley and Ploegh 2004;Ye et al 2004).…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…Transport of proteins from the ER back to the cytoplasm occurs during ERassociated degradation (ERAD), where ER proteins prone for degradation are transported through the translocon back to the cytoplasm for degradation by the proteasome [28]. In yeast, Sec63p and BiP co-precipitate with ER-associated proteasomes and mutations in Sec63p or BiP affect degradation of unfolded proteins in the ER [29,30]. BiP recognizes hydrophobic regions of misfolded or partially assembled proteins and promotes ER retention and protein folding [31].…”
Section: Sec63mentioning
confidence: 99%
“…It has been shown that the 26S proteasome disassembles in an ATP-dependent catalytic cycle, leading to 19S RP subcomplexes and free 26S protease regulatory subunit 5a (Babbitt et al, 2005). In contrast, 19S RPs are able to interact with Sec61 at the ER membrane (Ng et al, 2007). Wahlman et al (2007) demonstrated that ATP, the 19S RP, the ER luminal chaperone PDI, and Derlin-1 are sufficient to retrotranslocate a soluble ERAD substrate in vitro (Wahlman et al, 2007).…”
Section: Downloaded Frommentioning
confidence: 99%